Normalisation and the Translation of Phraseology in the COVALT Corpus - Marco, Josep (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2009)
AbstractIn this article, it is assumed that phraseological usage can be regarded as an indicator of normalisation in translated texts, as phraseological units are target-language standardised forms belonging to its lexical repertoire. Drawing on data yielded by the English-Catalan subcorpus of COVALT (Valencian Corpus of Translated Literature), it was found that Catalan translated texts are less phraseological than their corresponding English source texts, though only by a narrow margin. The narrowness of the margin seems to bear witness to some effort on the translators’ part to retain or recreate a noticeable degree of phraseological activity in translated texts. However, further research is needed into the motives underlying translator behaviour in this respect.